Survival impact on triple-modal strategy comprising hyperthermia, external radiation, and chemotherapy for unresectable locally advanced (UR-LA) pancreatic ductal adenocarcinoma. (June 2021) - Shimomura, Osamu; Oda, Tatsuya; Hashimoto, Shinji; Doi, Manami; Hiroshima, Yuichi; Numajiri, Haruko; Takahashi, Kazuhiro; Furuya, Kinji; Miyazaki, Yoshihiro; Owada, Yohei; Ogawa, Koichi; Ohara, Yusuke; et al.
Abstract: Background: Present treatment strategy for unresectable locally advanced (UR-LA) pancreatic ductal adenocarcinoma (PDAC) patients is controversial. Hence, a triple-modal therapy, which is a multidisciplinary strategy, was designed for patients with UR-LA PDAC by adding hyperthermia to conventional chemoradiotherapy at our institution. In this study we aimed to evaluate the effectiveness of this strategy. Methods: Data of 21 UR-LA PDAC patients who underwent the triple-modal treatment were retrospectively analyzed for evaluating the safety and oncological effect of the treatment. The treatment schedule included, five concurrent infusions of gemcitabine (800 mg/m 2 ) followed by hyperthermia (1 h) and X-ray (2 Gy) or proton beam radiation (2.7 Gy) on days 1, 8, 15, 29, and 36. Additional radiotherapies applied a total dose of 50 Gy/25 fr for X-ray radiation or 67.5 Gy/25 fr for proton beam radiation. Results: Median overall survival (OS) was 23.6 months. Conversion surgery was performed in 5 patients (23.8%), and a R0 margin could be achieved in 4 of them; however, their median OS (16.3 months) tended to be shorter than that of the patients who did not undergo resection (23.6 months, p  = 0.562). Further, the median OS of patients who underwent proton beam radiation (28.0 months) was significantly longer than that of patients who underwent X-ray radiation (13.9 months, p  = 0.045). Most adverse events were manageable, except for one grade 3 gastric ulcer. The median tumor size and marker reduction rates were −17% and −91%, respectively. The tumor responses were partial response, stable disease, and progressive disease in 3, 15, and 3 patients, respectively. Conclusion: Triple-modal strategy, especially when combined with proton beam radiation, is feasible and results in favorable survival outcomes in patients with UR-LA PDAC. Highlights: Triple-modal strategy is designed for unresectable locally advanced pancreatic cancer. Triple-modal strategy consist from hyperthermia and chemoradiation. Triple-modal strategy was tolerated with manageable adverse events. Improve survival in patients, resulting in a median overall survival of 23.6 months. Survivals when it combined with proton beam radiation reached to 30.9 months.